The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/8624313
|View full text |Cite
|
Sign up to set email alerts
|

Plasma C1q/TNF-Related Protein-9 Levels Are Associated with Atherosclerosis in Patients with Type 2 Diabetes without Renal Dysfunction

Abstract: Aim. C1q/tumor necrosis factor-related protein-9 (CTRP9), a paralog of adiponectin, is expressed in adipose tissue. CTRP9 exerts protective effects against obesity and atherosclerosis in rodents. We investigated the association between plasma CTRP9 levels and atherosclerosis in patients with type 2 diabetes. Methods. We included 419 patients with type 2 diabetes, 161 of whom had chronic kidney disease (CKD). Fasting plasma CTRP9 and total adiponectin levels were measured with enzyme-linked immunosorbent assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Moreover, a PPAR-agonist could affect the expression of CTRP9 [ 27 ] and, therefore, patients treated with this drug (agonist) were excluded from the study. The results of this study were in line with those of Chang Hee Jung et al, who reported a positive association of CTRP9 levels with BMI and arterial stiffness [ 19 ] and a study by Asada et al in which a positive association between serum CTRP9 levels and atherosclerosis in T2DM patients was demonstrated [ 18 ]. In contrast, decreased and increased levels of circulating CTRP9 after bariatric surgery and in patients with impaired fasting glucose were shown, respectively [ 20 ], as well as increased serum CTRP9 levels in newly diagnosed T2DM patients [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, a PPAR-agonist could affect the expression of CTRP9 [ 27 ] and, therefore, patients treated with this drug (agonist) were excluded from the study. The results of this study were in line with those of Chang Hee Jung et al, who reported a positive association of CTRP9 levels with BMI and arterial stiffness [ 19 ] and a study by Asada et al in which a positive association between serum CTRP9 levels and atherosclerosis in T2DM patients was demonstrated [ 18 ]. In contrast, decreased and increased levels of circulating CTRP9 after bariatric surgery and in patients with impaired fasting glucose were shown, respectively [ 20 ], as well as increased serum CTRP9 levels in newly diagnosed T2DM patients [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…These results indicate that serum levels of CTRP9 were elevated in CAD and T2DM patients. Preceding studies showed increased levels of serum CTRP9 in obesity and its attendant health risks [ 8 , 18 20 ], while decreased serum levels of CTRP9 was reported in CAD patients [ 16 ]. These observed discrepancies may have resulted from differences such as non-CAD subject selection/exclusion criteria and ethnicities between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean IMT of the common carotid artery (CCA) was measured by using a phase-locked echo-tracking system, which was equipped with a high-resolution real-time 13 MHz linear scanner (Prosound SSD 6500 and F75; Hitachi Aloka Medical, Ltd., Tokyo, Japan), as previously described [25]. The IMT value was determined by using a measurement software (Intimascope; Media Cross Co. Ltd, Tokyo, Japan), as described elsewhere [25, 26]. In brief, images were obtained 20 mm proximal to the origin of the bulb at the far wall of both CCAs.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies showed significantly lower CTRP9 expression levels in patients with CAD with or without pulmonary arterial hypertension (Li et al, ; Wang et al, ) whose major pathological change is vascular remodeling as well. Nevertheless, other researchers found that circulating levels of CTRP9 increased in CAD with or without T2DM individuals (Moradi et al, ) and were positively correlated with carotid intima‐media thickness (IMT) and arterial stiffness (Asada et al, ; Audette, Challis, Jones, Sibley, & Matthews, ). Remodeling is an active process of vascular structure changes, involving cell growth, death, migration, as well as the extracellular matrix production and degradation.…”
Section: Introductionmentioning
confidence: 99%